PENGEMBANGAN BUKU AJAR BAHASA INGGRIS MATEMATIKA BERBASIS COLLABORATIVE LEARNING UNTUK MAHASISWA PENDIDIKAN MATEMATIKA - Hera Deswita; Batdal Niati (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2018)
The development of textbooks is very important in order to achieve the objectives of the lecture, one of which is in the English for Mathematics course. The purpose of this research was to develop English for mathematics textbook base on Collaborative Learning for mathematics education students. Development of this textbook was 4-D model with stage; defining, designing, developing and disseminating. English for mathematics based on collaborative learning are validated by several experts namely mathematical material experts, language experts and lay out experts. The practicality of textbook obtained through the result of student response questionnaires. The result of this research was to produce English for mathematics textbook based on collaborative learning that were valid and practical to be used for mathematics student in learning